Influence of quality of oil products on reliability of aviation engines - Черняк, Л. М.; Стесюк, Ю. В. (Proceedings of National Aviation University (archive), 2013)
It was reviewed reasons of slime formation process in turbine and industrial oils as well as factors that affect the aging of oils during operation. It was defined types of contaminations, which change operational properties of oils in the result of aging as a chemical reaction. It was specified factors that influence an intensive oil aging and its premature rejection